Penerapan SAK ETAP Dalam Penyusunan dan Penyajian Laporan Keuangan - Fauzi, Rian; Pramiudi, Udi; Djanegara, Moermahadi Soerja (Institut Bisnis dan Informatika Kesatuan, 2018)
This research was conducted at the Toko Besi Sumber Baja Mandiri which is located at Jalan Raya Pangkalan 2 Kedung Halang, Bogor City. The purpose of this study was to find out how the process of preparing and presenting financial statements at the Toko Besi Sumber Baja Mandiri and knowing how the implementation of SAK ETAP regarding the preparation and presentation of financial statements at the Toko Besi Sumber Baja Mandiri if applied. This study uses a qualitative descriptive method in which the authors describe how the process of preparing and presenting financial statements at Toko Besi Sumber Baja Mandiri and how the implementation of SAK ETAP about the preparation and presentation of financial statements at the Toko Besi Sumber Baja Mandiri if applied. Research results show that the process of preparing and presenting financial statements at Toko Besi Sumber Baja Mandiri is very simple and the preparation and presentation of financial statements based on SAK ETAP at the Sumber Baja Mandiri iron shop if applied includes recording transactions into general journals, posting to general ledgers and presenting financial statements which consists of income statement and retained earnings, balance sheet, and cash flow statement. Keywords: financial statements, SAK ETAP